(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article briefly provides information about European types of cotoneaster growing in the Botanical Garden. E.Z. Gareeva NAS KR. Their decorative qualities and place of their growth are given.